Drought analysis using by NDVI index in the plain of Qorveh and Dehgolan. (تحقیقات کاربردی علوم جغرافیایی)
Drought phenomenon with different goals including planning, water sources management and dealing with the problems due to water shortage has been investigated by most scholars. This research examined the relationship between drought and the normalized difference vegetation index (NDVI)in Qorveh and Dehgolan region in Kurdistan, Iran. To determine years with meteorological drought, index of Standard Z during a 20 year period time (1387-1368) has been applied. The results of the statistical data in Ghorveh station in 2008 with total annual rainfall of 155 mm and Z index of -2.31, in 2000 with total rainfall of 253.1 and Z index of -1.5 and in 2001 with 239.5 rainfall and Z index of -1.22. Were determined as drought indeces. MODIS satellite images were used to assess the ecological drought. Associated with each image to a randomly selected sample of 500 places in the software ERDAS, NDVI values were calculated for these images. satellite image processing results and  Normalized Difference Vegetation Index (NDVI) indicates a low index values in the years 2000, 2001 and 2008 Were determined as ecological drought years of 2001 samples had the lowest NDVI and central parts of the area under irrigation has almost lost its vegetation.